Correlates of Precoital Behaviors, Intentions, and Sexual Initiation Among Thai Adolescents - Katharine A. Atwood (2018)
This paper examines the risk and protective factors associated with sexual behaviors among Thai youth ages 13-14 (N=420) living in Bangkok, Thailand. Cross-sectional data were collected using a random sample of households methodology. Three outcomes were assessed: (1) intention to engage in sexual intercourse, (2) pre-coital behaviors, and (3) sexual initiation. Bivariate analysis indicated that parental disapproval of sex, exposure to pornographic media, refusal self-efficacy and having a boyfriend/girlfriend had the strongest relationships with all three outcomes. Multivariate analyses found that parental disapproval of sex and exposure to pornographic media (internet or TV) were significantly associated with all three outcomes. Having a boyfriend or girlfriend was associated with pre-coital behaviors and intentions and sexual refusal self efficacy was correlated with pre-coital behaviors only. The potential competing influences of parent disapproval and exposure to pornographic media on adolescent sexual behaviors should be considered when adapting HIV prevention interventions for Thai youth. © The Author(s) 2012.